Efforts For Empowerment and Dry Waste Management Using A Waste Bank System in Kepuh Village, Kertosono District, Nganjuk Regency - Enny Istanti (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The issue of waste management is still a thorny problem for Indonesia. This is because most of the waste produced by households still ends up in the Final Disposal Site (TPA). Meanwhile, the capacity of landfills, especially in big cities, is getting full. In fact, it is not easy to find land to open a new TPA to accommodate the garbage collected from the community. The purpose of this community service is to teach the residents of Kepuh Village to process household dry waste. The qualitative method used in this activity uses socialization and guidance. The stages in data analysis using qualitative methods are data reduction, data presentation, and drawing conclusions. The results of the discussion in this community service are [1] Implementation of Waste Bank Socialization at the Chairman's House [2] Dry waste collection [3] Waste sorting at Residents' Houses and [4] Implementation of waste bank at Village Hall. The conclusion is that people do not understand the effect of dry waste disposal on the environment, fostering independence with dry waste processing practices.